Effects of falls prevention interventions on falls outcomes for hospitalised adults: protocol for a systematic review with meta-analysis. Issue 11 (12th November 2017) - Slade, Susan C; Carey, David L; Hill, Anne-Marie; Morris, Meg E
Abstract : Introduction: Falls are a major global public health problem and leading cause of accidental or unintentional injury and hospitalisation. Falls in hospital are associated with longer length of stay, readmissions and poor outcomes. Falls prevention is informed by knowledge of reversible falls risk factors and accurate risk identification. The extent to which hospital falls are prevented by evidence-based practice, patient self-management initiatives, environmental modifications and optimisation of falls prevention systems awaits confirmation. Published reviews have mainly evaluated community settings and residential care facilities. A better understanding of hospital falls and the most effective strategies to prevent them is vital to keeping people safe. Objectives: To evaluate the effectiveness of falls prevention interventions on reducing falls in hospitalised adults (acute and subacute wards, rehabilitation, mental health, operating theatre and emergency departments). We also summarise components of effective falls prevention interventions. Methods and analysis: This protocol has been registered. The systematic review will be informed by Cochrane guidelines and reported according to the Preferred Reporting Items for Systematic review and Meta-Analysis statement. Inclusion criteria: randomised controlled trials, quasi-randomised trials or controlled clinical trials that evaluate falls prevention interventions for use by hospitalised adults or employees. Electronic databases will be searched using key terms including falls, accidental falls, prevention, hospital, rehabilitation, emergency, mental health, acute and subacute. Pairs of independent reviewers will conduct all review steps. Included studies will be evaluated for risk of bias. Data for variables such as age, participant characteristics, settings and interventions will be extracted and analysed with descriptive statistics and meta-analysis where possible. The results will be presented textually, with flow charts, summary tables, statistical analysis (and meta-analysis where possible) and narrative summaries. Ethics and dissemination: Ethical approval is not required. The systematic review will be published in a peer-reviewed journal and disseminated electronically, in print and at conferences. Updates will guide healthcare translation into practice. Trail registration number: PROSPERO 2017: CRD 42017058887. Available from https://www.crd.york.ac.uk/prospero